Enhancing Pregnant Women’s Knowledge Through the Implementation of the Gerigi (Maternal Dental Care Movement) Program at Wolowa Community Health Center, Buton Regency - Syahrir Ramadhan Bukide (Jurnal EduHealth, 2025)
Maternal oral health is a critical yet often overlooked component of prenatal care, despite its significant association with adverse pregnancy outcomes such as preterm birth and Low Birth Weight (LBW). At the Wolowa Community Health Center (Puskesmas) in Buton Regency, a lack of awareness among pregnant women regarding the importance of dental care has led to low utilization of dental clinic services. This study aimed to evaluate the effectiveness of the "GERIGI" (Gerakan Peduli Gigi Ibu Hamil or Maternal Dental Care Movement) innovative program in enhancing maternal oral health knowledge. This study employed a quasi-experimental design with a one-group pre-test/post-test approach. A sample of 15 pregnant women was selected using purposive sampling. The intervention involved integrating dental health education into the Antenatal Care (ANC) service workflow, utilizing pamphlets and dental phantoms as educational aids, alongside direct clinical examinations. The findings demonstrated a significant increase in the mean knowledge score from 69.33% at pre-test to 86.33% at post-test. Effectiveness analysis using the Normalized Gain (N-gain) yielded a score of 0.54, indicating that the program falls within the "moderate effectiveness" category. The GERIGI program effectively improves maternal cognition through a collaborative, cross-program approach between the Maternal and Child Health (MCH) unit and the Dental Unit. It is concluded that integrating dental services into routine prenatal care is an effective promotive and preventive strategy and is recommended to be institutionalized as a Standard Operating Procedure (SOP) in primary healthcare facilities.